Biomaterials for Neural Tissue Engineering - Doblado, Laura Rodríguez; Martínez-Ramos, Cristina; Pradas, Manuel Monleón (Frontiers in Nanotechnology, 2021)
The therapy of neural nerve injuries that involve the disruption of axonal pathways or axonal tracts has taken a new dimension with the development of tissue engineering techniques. When peripheral nerve injury (PNI), spinal cord injury (SCI), traumatic brain injury (TBI), or neurodegenerative disease occur, the intricate architecture undergoes alterations leading to growth inhibition and loss of guidance through large distance. To improve the limitations of purely cell-based therapies, the neural tissue engineering philosophy has emerged. Efforts are being made to produce an ideal scaffold based on synthetic and natural polymers that match the exact biological and mechanical properties of the tissue. Furthermore, through combining several components (biomaterials, cells, molecules) it is facilitated axonal regrowth to obtain a functional recovery of the neural nerve diseases. The main objective of this review is to investigate the recent approaches and applications of neural tissue engineering approaches.